Perjanjian Malaysia 1963 (MA63) sebagai Dokumen Sejarah dan Kedudukan Perundangannya dalam Konteks Masa Kini - A Rahman Tang Abdullah; Bilcher Bala; Pandikar Amin Mulia (2018)
The Malaysia Agreement of 1963 (MA63) is not merely appreciated as a Historical Document. In fact, its significance lays down in its value in Legality in relations to the foundation of the Federation of Malaysia in 1963. This is because MA63 contains legal provisions concerning the special rights and constitutional safeguards granted to Sabah and Sarawak pertaining to the inclusion of those two states into the federation. Nevertheless, it seems that there is confusion on its legal application in current context. This relates to the political statements ‘to return the status of Sabah and Sarawak according to MA63’. This article discusses MA63 as a historical document and its legal status in contemporary context. This discussion is based on an analysis of the content of the MA63 document as well as its factual knowledge. It aims to prove the understanding of the MA63 that been applied in an anachronistic manner due to the complexity of linking the document and historical events to contemporary context